Simultaneous immobilization of arsenic, lead, and cadmium in soil by magnesium-aluminum modified biochar: Influences of organic acids, aging, and rainfall. (February 2023) - Peng, Cheng; Gong, Kailin; Li, Qiannan; Liang, Weiyu; Song, Huihui; Liu, Fang; Yang, Jie; Zhang, Wei
Abstract: Magnesium-aluminum modified biochar (MABs) has an outstanding effect on the simultaneous immobilization of arsenic (As), lead (Pb), and cadmium (Cd) in soil, but the stability of remediation effect of MAB under various natural conditions is still unknown. In this study, we investigated the effects of organic acids, dry-wet cycles (DW), freeze-thaw cycles (FT), and rainfall (pH 4, 7, and 8) on the immobilization of As, Pb, and Cd by MAB. The results showed that oxalic acid decreased the immobilization efficiencies of As, Pb, and Cd by 15.5%–38.5%; meanwhile, humic acid reduced the immobilization efficiency of Pb by 89.7%, but elevated that of Cd by 19.5%. The immobilization mechanisms of MAB-5 on three metals were mainly involved in ion exchange and surface-complexation. Compared with the 7th round, the immobilization efficiencies of As, Pb, and Cd by MAB in the 28th round was decreased by 17%–28% in DW, but was increased by 11%–18% in FT. In addition, MAB was transformed into hydrotalcite after FT and DW. After experiencing simulated rainfall, MAB caused more As, Pb, and Cd to be retained in the upper soil layer, and the immobilization effect of MBA was more significant under the stimulated rainfall with higher pH. The study provides a more theoretical basis for the application of MAB in the actual site remediation. Graphical abstract: Image 1 Highlights: Dry-wet aging reduced the immobilization efficiency of heavy metals by MAB-5. Freeze-thaw aging enhanced the immobilization efficiency of heavy metals by MAB-5. The addition of MAB-5 could slow down the vertical migration of heavy metals.